Striatal dysfunction in X‐linked dystonia‐parkinsonism is associated with disease progression. (25th February 2017) - Brüggemann, N.; Rosales, R. L.; Waugh, J. L.; Blood, A. J.; Domingo, A.; Heldmann, M.; Jamora, R. D.; Münchau, A.; Münte, T. F.; Lee, L. V.; Buchmann, I.; Klein, C.
Abstract : Background and purpose: X‐linked dystonia‐parkinsonism (XDP) is an inherited neurodegenerative adult‐onset movement disorder associated with striatal atrophy. As the dopaminergic system has not yet been systemically studied in this basal ganglia model disease, it is unclear whether nigrostriatal dysfunction contributes to parkinsonism in XDP. Methods: Pre‐ and post‐synaptic dopaminergic function was assessed in XDP. A total of 10 123 jod‐benzamide (IBZM) single‐photon emission computed tomography (SPECT) images were obtained for nine patients aged 42.3 ± 9.5 years (SD; range 30–52) and one asymptomatic mutation carrier (38 years), and four ioflupane (FP‐CIT) SPECT images were obtained for four patients, aged 41.5 ± 11.6 years (range 30–52 years). Structural magnetic resonance imaging was also performed for all mutation carriers and 10 matched healthy controls. Results: All patients were men who suffered from severe, disabling segmental or generalized dystonia and had varying degrees of parkinsonism. IBZM SPECT images were pathological in 8/9 symptomatic patients with distinct reduced post‐synaptic tracer uptake in the caudate nucleus and putamen, and unremarkable in the asymptomatic mutation carrier. Longer disease duration was correlated with lower IBZM binding ratios. All subjects exhibited slightly reduced FP‐CIT uptake values compared to controls for each analyzed region (−37% to −41%) which may be linked to basal ganglia volume loss. Visual inspection revealed physiological FP‐CIT uptake in 1/4 patients. Conclusions: This nuclear imaging study provides evidence that the functional decline of post‐synaptic dopaminergic neurotransmission is related to disease duration and ongoing neurodegeneration. Given the severe striatal cell loss which could be verified with post‐synaptic nuclear imaging, both parkinsonism and dystonia in XDP are probably mainly due to striatal dysfunction.